How to manage Ebstein's Anomaly in Pregnancy: A Literature Review with Case Study - Alireza Nematollahi; Shadi Zamansaraei; Farima Safari; Parvin Bahrami (Shiraz University of Medical Sciences, 2022)
Background: Ebstein's anomaly (EA) is a congenital heart defect that causes cyanosis and arrhythmia. The treating physician has difficulty when it comes to pregnant women since patients frequently reach reproductive age. How to manage these patients during pregnancy or approach patients who are planning to become pregnant is an important issue. The aim of this study was to evaluate previous and current literature reviews, as well as case studies, to better understand how to treat Ebstein's abnormality in pregnancy. Methods: This study is a literature review with case report. Here, we review the literature on this subject to discuss how to manage Ebstein's anomaly in pregnancy. We analyzed the literature from different perspectives. We also focused on three of Ebstein's anomaly-affected women's pregnancies. Results: Three women had four pregnancies, all of which were delivered vaginally or through cesarean section. There were no preterm births. 2.540.88 kg was the average birth weight. There were no cardiac abnormalities in any of the three infants. One patient had Ebstein's abnormality and congenitally corrected transposition of the great arteries (ccTGA). Conclusion: In Ebstein's abnormality, pregnancy is often well tolerated. However, the maternal risks of pregnancy correlated with the severity of anatomical malformations and the presence of cyanosis or simultaneous other cardiac anomalies.